PEMBUATAN CERITA RAKYAT INDONESIA MALIN KUNDANG DIGITAL DENGAN 3D MODELING OBJECT BERBASIS ANDROID - Erick Setiawan; Liliana -; Djoni Setiabudi (Jurnal Infra, 2014)
The background of digitalizing one of the Indonesian folklores, Malin Kundang in 3D object modeling for Android is to reintroduce the story, which is not as famous as any other fairy tales from other countries. This application is usable for Androids, which have been widely used nowadays. What makes this program different with any similar programs is the using of 3D object digital and its animation, and users can actively run the program and play the story, in which the learning method has been commonly applied for kids these days. This program uses Unity3D as the main software maker. On the other hand, Blender software is used to make the 3D object and its animation. This Blender application is also applied to convert the 3D type to .fbx so that the animation is able to be read and used. To support the 3D object digital, this applications is designed in 3D visual with narrative storyline and mini games. The 3D visualization presents the story in dialogues per scene by using 3D object and its animation, meanwhile the mini games put the story through the culture at that time. The output of this application is to let its users be aware of one of Indonesian cultures, which in this case is Malin Kundang the folklore, in more unique and authentic way.